The retinoic acid receptor (RAR) α-specific agonist Am80 (tamibarotene) and other RAR agonists potently inhibit hepatitis B virus transcription from cccDNA - Nkongolo, Shirin; Nußbaum, Lea; Lempp, Florian A.; Wodrich, Harald; Urban, Stephan; Ni, Yi (Antiviral research, 2019)
Chronic infection with the human Hepatitis B virus (HBV) is a major global health problem. Hepatitis D virus (HDV) is a satellite of HBV that uses HBV envelope proteins for cell egress and entry. Using infection systems encoding the HBV/HDV receptor human sodium taurocholate co-transporting polypeptide (NTCP), we screened 1181 FDA-approved drugs applying markers for interference for HBV and HDV infection. As one primary hit we identified Acitretin, a retinoid, as an inhibitor of HBV replication and HDV release. Based on this, other retinoic acid receptor (RAR) agonists with different specificities were found to interfere with HBV replication, verifying that the retinoic acid receptor pathway regulates replication. Of the eight agonists investigated, RARα-specific agonist Am80 (tamibarotene) was most active. Am80 reduced secretion of HBeAg and HBsAg with IC50s<10nM in differentiated HepaRG-NTCP cells. Similar effects were observed in primary human hepatocytes. In HepG2-NTCP cells, profound Am80-mediated inhibition required prolonged treatment of up to 35 days. Am80 treatment of cells with an established HBV cccDNA pool resulted in a reduction of secreted HBsAg and HBeAg, which correlated with reduced intracellular viral RNA levels, but not cccDNA copy numbers. The effect lasted for >12 days after removal of the drug. HBV genotypes B, D, and E were equally inhibited. By contrast, Am80 did not affect HBV replication in transfected cells or HepG2.2.15cells, which carry an integrated HBV genome. In conclusion, our results indicate a persistent inhibition of HBV transcription by Am80, which might be used for drug repositioning.